Evaluation of 4 Point-of-Care Units for the Determination of Blood L-Lactate Concentration in Cattle - Karapinar, T.; Kaynar, O.; Hayirli, A.; Kom, M. (Wiley-Blackwell, 2013)
BackgroundDespite being used commonly in bovine medicine, information on reliability of point-of-care (POC) lactate meters is limited. ObjectiveTo determine the validity of 4 commercially available POC lactate meters in cattle. AnimalsCattle with various diseases (n=120). MethodsBlood samples collected from the jugular vein were processed immediately on POC lactate meters. Plasma l-lactate concentration was measured by the enzymatic-colorimetric method (ELISA). Data were subjected to Friedman's test for comparison, Passing-Bablok regression and Bland-Altman plot analyses for reliability, and receiver operating characteristics analysis for sensitivity (Se) and specificity (Sp). ResultsThe POC lactate meters were highly correlated with ELISA (r=0.98-0.99) despite disagreements among units. When regressed on ELISA, blood l-lactate concentrations generated from Accutrend Plus and Lactate Pro were linear up to 16.6 and 15.7mmol/L, respectively, whereas those generated from i-STAT and Lactate Scout were linear up to 19.5 and 19.7mmol/L, respectively. All POC lactate meters had a Se of 100% with Sp of 95.7-98.6% at a plasma l-lactate cut-off concentration of 4mmol/L. i-STAT had the best accuracy (99.0%) and precision (99.8%), the best linear fit (y=-0.13+1.04X) yielding the lowest bias (-6.6%) as well as the highest Se (100%) and Sp (98.6%). Conclusions and Clinical ImportanceDespite high correlation with the reference method, dilution is needed for Accutrend Plus/Lactate Pro and i-STAT/Lactate Scout if concentrations >15 and 20mmol/L, respectively. i-STAT provided the most accurate and precise results.
Keywords: Accuracy; Bovine; Portable lactate meter; Precision; Sensitivity; Specificity